Symbolic meaning of pork crossing national borders in the migration process: From a national collective anti-key symbol to the manifestation of Russian Jewish identity in Israel - Bernstein, Julia (Hagar: Studies in Society and Culture, 2012)
The analysis of the meaning of pork for Russian Jews in Israel suggests that far from being a private matter ("You can’t argue about taste"), the aspiration to define, preserve and reinforce collective identities includes imposing a national cuisine. I show how pork consumption can serve a community of migrants as a marker of their home system or as an imagined status marker whose collective affiliation is perpetually negotiated, rebuilt and redefined.